2016
DOI: 10.1002/cbin.10676
|View full text |Cite
|
Sign up to set email alerts
|

The fast track to canonical Wnt signaling in MC3T3‐E1 cells protected by substance P against serum deprivation‐induced apoptosis

Abstract: The canonical Wnt pathway is vital to bone physiology by increasing bone mass through elevated osteoblast survival. Although investigated extensively in stem cells, its role in osteoblastic MC3T3-E1 cells has not been completely determined. To explore how this pathway is regulated by different conditions, we assessed the anti-apoptotic effects of substance P on the canonical Wnt pathway in MC3T3-E1 cells by treating cells with serum deprivation or serum starving with "substance P," a neuropeptide demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…At a later time point (21 days) osteoblasts responded differently to SP which is in accordance to data from Yang et al . who reported that stimulation with 10 −10 M SP prevented MC3T3 osteoblasts against serum deprivation-induced apoptosis 28 . Backman and colleagues also demonstrated positive effects of SP on cell survival 29 .…”
Section: Discussionmentioning
confidence: 99%
“…At a later time point (21 days) osteoblasts responded differently to SP which is in accordance to data from Yang et al . who reported that stimulation with 10 −10 M SP prevented MC3T3 osteoblasts against serum deprivation-induced apoptosis 28 . Backman and colleagues also demonstrated positive effects of SP on cell survival 29 .…”
Section: Discussionmentioning
confidence: 99%
“…2A, Supplemental Table II). The genes linked to apoptosis were decreased, consistent with a survival role for SP (52). The growth factors within the network underscored the complex mechanism by which SP stimulates hematopoiesis (17).…”
Section: Hematopoietic-associated Genes In Sp-stimulated Stromamentioning
confidence: 67%